Diagnostic value of the isoenzymatic index of lactate dehydrogenase in blood serum in a special process for training cadet pilots - Wochyński, Zbigniew; Majsterek, Ireneusz; Gerszon, Joanna; Wojtczak, Radosław; Kabziński, Jacek; Błaszczyk, Jan; Sobiech, Krzysztof A.; Jabłońska, Ewa; Ratajczak-Wrona, Wioletta (Frontiers in Physiology, 2024)
ObjectivesSpecial aerial gymnastics instruments (SAGI) are permanent elements of specialist training for cadet pilots. Appropriate physical activity and fitness are essential for performing the tasks of military pilots. Therefore, one of the main goals of cadet training is to develop adaptation to the extreme conditions of a military pilot’s work. This study aimed to determine the effect of the SAGI training process for cadet pilots on their aldolase and lactate dehydrogenase (LDH) activity, LDH enzymatic index (iZO), C-reactive protein (CRP) and haptoglobin (HP) levels, and physical fitness.Material and MethodsParticipating in this study were 55 cadets, aged 20 ± 0.70 years, in two groups. In group A (n = 41, tested) cadets were trained on SAGI with an emphasis on endurance and strength. In group B (n = 14, control), the cadets performed general fitness training. Blood samples were collected before and after training series I, II, and III. LDH and its isoenzyme activity, aldolase, CRP, and HP levels were assayed in blood serum using commercially available tests, and the iZO value was calculated.ResultsA downward trend was observed in HP and CRP levels in both groups after all three training series. In group A after training, LDH and aldolase activity was lower than in group B. However, in both groups, a significant increase of iZO values was observed after training series II and III in group A, p < 0.001, p < 0.05, respectively, and in group B, p < 0.05 and p < 0.0005, respectively. Physical fitness also improved in both groups.ConclusionThe course of the SAGI exercises showed that the iZO value depends on physical exercise intensity, its type, and cadet adaptation.